US‐China cooperation on low carbon development planning and analysis in China's provinces and cities. Issue 1 (10th November 2021) - Peterson, Thomas D.; Roe, Stephen M.; Ugliano, Arianna; Yu, Qingchan; Liao, Cuiping
Abstract: From 2009 to 18, the US based Center for Climate Strategies and Beijing based Global Environmental Institute led a cooperative US‐China relations program on low carbon development (LCD). The template for bilateral cooperation leveraged traditional policy innovation and mainstreaming procedures in China through early stage training and counterpart exchange, co‐development and piloting of tools, national endorsement for official use, training and capacity building, and cooperative planning actions. The experience suggests that the bilateral cooperation model through high level technical and institutional cooperation between governmental and nongovernmental experts worked well and can be replicated with customization to new bilateral relationships at different jurisdictional levels and for different issue areas. However, to succeed it requires years of stable investment and continuous counterpart engagement, and its application to new bilateral cooperation must address a variety of barriers. The China subnational LCD co‐development process was enabled by an existing US template for state level comprehensive climate action planning applied in over 20 US states. Its domestication in China resulted in creation of the China Subnational LCD Planning and Analysis Toolkit, a pilot in Chongqing, official endorsement by China's National Development and Reform Commission (NDRC), and further recognition through a US State Department – China NDRC EcoPartnership. Ultimately, it involved many partners, including the Chinese Academy of Sciences Institute for Policy and Management, the Guangzhou Institute of Energy Conversion, and over 30 provinces and cities. It led to new China efforts addressing renewable energy implementation in South China, and for LCD and renewable energy cooperation in Southeast Asia.